OPTIMIZATION OF HPMC IN SERUM GEL CONTAINING BUTTERFLY PEA FLOWER EXTRACT (CLITORIA TERNATEA L.) AS FACIAL MOISTURIZER AND IT’S PHYSICAL STABILITY - Rahmawati, Dewi; Ambari, Yani; Ningsih, Arista Wahyu; Mayasari, Shinta; Aulia, Andira; Putri, Masitah Nurwidiya; Ressi, Monica (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Skincare refers to a series of skin treatments (epidermis) and the middle layer of the skin (dermis) aimed at protecting and maintaining the body, and is categorized as a cosmetic product. One of the most commonly used cosmetic preparations is skincare serum, which helps maintain skin elasticity and hydration. A rising trend in the industry is the development of serums, and one potential plant to be used as a safe active ingredient in cosmetics is the butterfly pea flower (Clitoria ternatea L), which is rich in flavonoids with antioxidant activity. The objective of this study was to determine whether butterfly pea flower extract serum can be formulated into a facial serum with moisturizing properties and to evaluate the physical stability of the serum preparation. The method used is Laboratory experiments were performed. The butterfly pea flower extract was obtained through maceration with 70% ethanol and then formulated into facial serum using different concentrations of HPMC base at 3%, 4%, and 5%. The results of serum stability tests were obtained using physical stability methods. Physical property tests included organoleptic testing (lavender scent, deep blue color, slightly thick, or serum-like texture), with stable organoleptic properties observed during storage, without any changes ...